Logic, language, information and computation 19th International Workshop, WoLLIC 2012, Buenos Aires, Argentina, September 3-6, 2012. proceedings - Queiroz, Ruy; Ong, Luke (Lecture notes in Computer Science, 2012)
Edited in collaboration with FoLLI, the Association of Logic, Language and Information this book constitutes the refereed proceedings of the 19th Workshop on Logic, Language, Information and Communication, WoLLIC 2012, held in Buenos Aires, Argentina, in September 2012. The papers accompanying 8 invited lectures are presented together with 16 contributed papers; the latter were carefully reviewed and selected from 46 submissions. The papers report advances in inter-disciplinary research involving formal logic, theory of computation, foundations of mathematics, and computational linguistics.